Loss of ASAP1 in mice impairs adipogenic and osteogenic differentiation of mesenchymal progenitor cells through dysregulation of FAK/Src and AKT signaling - Schreiber, Caroline; Saraswati, Supriya; Harkins, Shannon; Gruber, Annette; Cremers, Natascha; Thiele, Wilko; Rothley, Melanie; Plaumann, Diana; Korn, Claudia; Armant, Olivier; Augustin, Hellmut; Sleeman, Jonathan P. (PLoS Genetics, 2019)
ASAP1 is a multi-domain adaptor protein that regulates cytoskeletal dynamics, receptor recycling and intracellular vesicle trafficking. Its expression is associated with poor prognosis for a variety of cancers, and promotes cell migration, invasion and metastasis. Little is known about its physiological role. In this study, we used mice with a gene-trap inactivated ASAP1 locus to study the functional role of ASAP1 in vivo, and found defects in tissues derived from mesenchymal progenitor cells. Loss of ASAP1 led to growth retardation and delayed ossification typified by enlarged hypertrophic zones in growth plates and disorganized chondro-osseous junctions. Furthermore, loss of ASAP1 led to delayed adipocyte development and reduced fat depot formation. Consistently, deletion of ASAP1 resulted in accelerated chondrogenic differentiation of mesenchymal cells in vitro, but suppressed osteo- and adipogenic differentiation. Mechanistically, we found that FAK/Src and PI3K/AKT signaling is compromised in Asap1GT/GT MEFs, leading to impaired adipogenic differentiation. Dysregulated FAK/Src and PI3K/AKT signaling is also associated with attenuated osteogenic differentiation. Together these observations suggest that ASAP1 plays a decisive role during the differentiation of mesenchymal progenitor cells.